ANALISIS PEMAHAMAN KONSEP MATEMATIS DALAM MENYELESAIKAN SOAL PADA MATERI TEOREMA PYTHAGORAS SMP KELAS VII - Setiawan, Niko; Nuryadi, Nuryadi (FKIP Universitas Al Washliyah Medan, 2024)
This research is descriptive research with a quantitative approach to analyze students' conceptual understanding of the Pythagorean Theorem material for class VII. The population in this study was class VII students at SMP Negeri 1 Sedayu for the 2023/2024 academic year, and this research consisted of 32 sample students from class VII F. The data collection techniques used in this research were observation, tests and interviews. The instruments used in this research were observation sheets, tests and interviews. This research aims to analyze the level of students' understanding of concepts in the Pythagorean Theorem material for class VII middle school. From the data analysis results in this study, it shows that from a sample of 32 students, 7 students with a presentation of 21.8% were in the high category, 12 students with a presentation of 37.5% were in the medium category, and 13 students with a percentage of 40.62% were in the The low category means that students' understanding of mathematical concepts is still low. This is justified and supported by the results of the 5 indicators tested. Based on the data from the calculation of indicators for understanding the concept, there are 3 indicators in the low category and 2 other indicators in the medium category.